A historiographical sketch of the Gierek’s decade. A contribution to the issues of Polish historical literature about the 1970s in Poland - Domke, Radosław (Myths and Stereotypes in the Collective Representations, 2019)
In article I amtrying to summarise polish historiography about Gierek’s decade. Since the end of this period only 35 years have passed, but even now we can define some plots on that field. Historical literature upon that thing can be divided into four periods. In some of them we can find more or less critical discourses. The paper help us figure out which was dominant in current period. In that way we can recapitulate how was seen „the decade of accelarated development” in polish historiography, was it a „paradise”, or opposite.